Industrial X-Ray Computed Tomography - Carmignato, Simone; Dewulf, Wim.; Leach, Richard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book covers all aspects of industrial X-Ray computed tomography (XCT) including history, basics, different instrument architectures, hardware and software, error sources, traceability and calibration, and applications. The book is intended for users and developers of XCT instrumentation and software in both industry and academia, being also suitable for postgraduate students.
Introduction -- Principles of X-ray computed tomography -- Technical concepts and components -- Processing and visualization of CT data -- Computer simulation -- Error sources -- Performance verification -- Traceability of CT dimensional measurements -- CT for non-destructive testing and materials characterization -- CT for dimensional metrology -- Other industrial applications.
Keywords: Materials -- Analysis; Manufactures; Optical materials; Atoms; Molecules; Characterization and Analytical Technique; Machines, Tools, Processes; Optical Materials; Atomic, Molecular and Chemical Physics